Harry Potter and the half-blood prince [video recording] - Rowling, J. K. (Burbank, CA : Warner Home Video, 2009)
As Lord Voldemort tightens his grip on both the Muggle and wizarding worlds, Hogwarts is no longer a safe haven. Harry suspects perils may even lie within the castle, but Dumbledore is more intent upon preparing him for the final battle fast approaching. Together they work to find the key to unlock Voldemort's defenses and to this end, Dumbledore recruits his old friend and colleague Horace Slughorn, who he believes holds crucial information. Even as the decisive showdown looms, romance blossoms for Harry, Ron, Hermione and their classmates. Love is in the air, but danger lies ahead and Hogwarts may never be the same again.
Directed by David Yates ; Produced by David Heyman and David Barron
Keywords: Potter, Harry (Fictitious character) -- Drama; Magical Adventure; Hogwarts School of Witchcraft and Wizardry (imaginary organization) -- Drama; Wizards -- England -- Drama